Human Trafficking dalam Perspektif Psikologi - Isyatul Mardiyati (Raheema, 2017)
The modern slavery or human trafficking could give negative impacts on every aspects of human life. Furthermore, psychologically, this crime could lead to stress state, depression, and trauma on the victims. However, only some of trauma has prolonged effect. Besides, some of them has a temporary effect and needs only a short of time to recovery. Thus, the basic knowledge which is understood wholly towards human trafficking need to be done. In order to prevent the message distorted and wrong approach to solve the problem. Besides, the using of suitable method to perform an action for victims’ recovery is really required, so the victims could gain a better life in the future.